Case Report: Dendritic Cells and Macrophages Capture Sperm in Chronically Inflamed Human Epididymis - Zheng, Wenzhong; Zhang, Shiqiang; Chen, Xiaobao; Jiang, Shaoqin; Li, Zhihao; Li, Mengqiang (Frontiers in Immunology, 2021)
Chronic inflammation of the male genital tract is thought to be a primary aetiological factor of male infertility. The abundance and activation of macrophages and dendritic cells (DCs) in patients with chronic inflammation of genital tract (CIGT) were closely associated with oligozoospermia and asthenospermia. Chronic epididymitis appears to be more important than seminal vesiculitis or prostatitis due to the direct interaction between spermatozoa and epididymal inflammatory cells. In this study, we present a case report of a 41-year-old male with oligoasthenospermia and chronic epididymitis. Hematoxylin-eosin (HE) staining and immunofluorescence analyses showed that antigen presenting cells (APCs) including macrophages and DCs were capture spermatozoa in the lumen of cauda epididymidis. To our knowledge, this is the first case report that directly observed DCs capture spermatozoa in the lumen of inflamed epididymidis. This finding directly explains the cause of oligospermia in patients with chronic epididymitis.